2021
DOI: 10.18474/0749-8004-56.2.185
|View full text |Cite
|
Sign up to set email alerts
|

Residual and Direct Contact Toxicities of Crude Extracts and Essential Oils from Acorus calamus L. (Acoraceae) Rhizomes against Cassava Red Mites (Acari: Tetranychidae)

Abstract: Tetranychus truncatus Ehara (Acari: Tetranychidae) is a serious economic pest of many plants in Thailand and other countries. The use of plant extracts is an alternative to conventional synthetic pesticides for controlling mite pests. This study was conducted to evaluate the residual and direct contact toxicities of crude extracts and essential oils obtained from Acorus calamus L. (Acoraceae) rhizomes against T. truncatus eggs and adult females under laboratory conditions. Residual toxicity was assayed by appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…High varroicidal activity was recorded in Sweet flag, more than 50% mortality at 2 HAT and also 100% mortality at 3 HAT followed by coleus which registered a 100% mortality at 12 HAT. Perusal of available literatures reveal that, scanty information are available in this direction on the varroicidal action of sweet flag (Acorus calamus and coleus (Coleus aromaticus), though there are numerous studies conducted with the aforesaid ingredients for the management of storage pests (El-Nahal et al, 1989;Singh et al, 2021;Shukla et al, 2016) and plant mites (Pushpa and Nandihalli, 2008;Thevan et al, 2005;Janlaor and Auamcharoen, 2021). Swamy et al (2006) reported that sweet flag (Acorus calamus) and tulsi (Ocimum sanctum), along with some other botanicals, can be used for the effective management of greater wax moth, which is another serious pest of honey bees.…”
Section: Resultsmentioning
confidence: 99%
“…High varroicidal activity was recorded in Sweet flag, more than 50% mortality at 2 HAT and also 100% mortality at 3 HAT followed by coleus which registered a 100% mortality at 12 HAT. Perusal of available literatures reveal that, scanty information are available in this direction on the varroicidal action of sweet flag (Acorus calamus and coleus (Coleus aromaticus), though there are numerous studies conducted with the aforesaid ingredients for the management of storage pests (El-Nahal et al, 1989;Singh et al, 2021;Shukla et al, 2016) and plant mites (Pushpa and Nandihalli, 2008;Thevan et al, 2005;Janlaor and Auamcharoen, 2021). Swamy et al (2006) reported that sweet flag (Acorus calamus) and tulsi (Ocimum sanctum), along with some other botanicals, can be used for the effective management of greater wax moth, which is another serious pest of honey bees.…”
Section: Resultsmentioning
confidence: 99%